GAMBARAN PENGETAHUAN SIKAP DAN PERILAKU PENDERITA INFEKSI SALURAN PERNAPASAN AKUT (ISPA) DI DESA GUMELEM WETAN KECAMATAN SUSUKAN KABUPATEN BANJARNEGARA TAHUN 2021 - Barni; Muslimah Mardiah (Jurnal Ilmiah Medsains, 2022)
Acute respiratory infection (ARI) is an acute respiratory disease caused by an infectious agent that is transmitted from humans. The incidence of ARI at the Susukan 1 Health Center was ranked first, namely in 2019 as many as 4,898 cases. The purpose of this study was to describe the knowledge, attitudes and behavior of ARI sufferers in Gumelem Wetan Village, Susukan District, Banjarnegara Regency in 2021. This study included descriptive research with a cross sectional approach. The study population was ARI sufferers as many as 125 respondents in January - May 2021 in Gumelem Wetan Village. The number of samples taken was 41 patients with ARI. The data used in this study are primary data obtained from interviews with a questionnaire guide. Data analysis was carried out in a univariate way. The results showed that the description of the knowledge of ARI sufferers in the good category was 43.9%, the attitude of the ARI sufferers was in the good category 48.8%, and the behavior of ARI patients was in the good category 46.3%.